Pendelegasian Wewenang Pembentukan Undang-Undang oleh Undang-Undang - Lovika Augusta Purwaningtyas; Bayu Dwi Anggono; A'an Efendi (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2023)
There is an unclear formulation in Article 10 paragraph (1) letter b of Act Number 12 of 2011 as amended by Act Number 15 of 2019, that the act can delegate the authority to form acts. This is contrary to Hans Kelsen's theory, namely legal norms accept delegation from norms that are considered valid or have a higher hierarchy, in other words the legal norms contained in the P3 Act cannot get validity. The purpose of this study is related to the main problem, namely conducting a study to find and analyze the delegation of authority to form Acts by Act. The type of research in this legal research is normative juridical research. Normative legal research or doctrinal legal research uses three problem approaches, namely the legal approach, conceptual approach, and comparative approach with the Netherlands and France. Based on the above thinking, the author uses a normative legal research method. In the discussion the author finds that the Act cannot delegate the authority to form Acts, because it is contrary to the principle of lex superior derogat legi inferiori, in the legal politics of delegating the formation of legislation there is also nothing that explains that this can be enforced. These problems include the delegation of authority to form acts by act, causing many polemics, namely the occurrence of overlapping and disharmony of acts with one another, and the occurrence of over-regulation in the acts and regulations in Indonesia.